Performance evaluation of a novel terrain aiding algorithm for GNSS tracking in forested environments - Danezis, Chris; Gikas, Vassilis (My University, 2012)
This research investigates the ability of Digital Surface Models (DSM) to aid GNSS tracking in forested environments. Particularly, a new augmentation methodology named "Terrain-Aiding" (TA) is proposed, evaluated and testified. Although "Terrain-Aiding" is a term already used in airborne military navigation, in this paper it is defined with an entirely different meaning; it forms an extension to the well-known technique of Height-Aiding (HA). In order to validate the proposed algorithm and associated software a set of dedicated experiments were carried out in a forested area located nearby Athens, Greece. To accommodate data collection, a specifically designed on-purpose build backpack platform was designed to carry two receivers of different (mapping- and geodetic-) grade characteristics. High accuracy DSM tiles were used to represent the terrain surface. Consequently, the TA algorithm was assessed in terms of GNSS positional availability, accuracy and external reliability in absolute terms (i.e. against a well-defined benchmark trajectory). The results obtained indicate an improvement in GNSS availability of the order of 37%, when only three satellites are available, whereas GNSS accuracy is significantly improved in cases of marginal conditions. Furthermore, the external reliability was considerably improved by more than 80%.
Keywords: Satellites; Navigation; Geometric dilution